Designing hydrogel for application in spinal surgery - Rongpeng Dong; Shuang Zheng; Xueliang Cheng (Materials Today Bio)
Spinal diseases and injuries are prevalent in clinical settings and impose a substantial burden on healthcare systems. Current treatments for spinal diseases are predominantly limited to surgical interventions, drug injections, and conservative treatments. Generally, these treatment modalities have limited or no long-term benefits. Hydrogel-based treatments have emerged as potentially powerful paradigms for improving therapeutic outcomes and the quality of life of patients. Hydrogels can be injected into target sites, including the epidural, intraspinal, and nucleus pulposus spaces, in a minimally invasive manner and fill defects to provide mechanical support. Hydrogels can be designed for the localized and controlled delivery of pharmacological agents to enhance therapeutic effects and reduce adverse reactions. Hydrogels can act as structural supports for transplanted cells to improve cell survival, proliferation, and differentiation, as well as integration into adjacent host tissues. In this review, we summarize recent advances in the design of hydrogels for the treatment of spinal diseases and injuries commonly found in clinical settings, including intervertebral disc degeneration, spinal cord injury, and dural membrane injury. We introduce the design considerations for different hydrogel systems, including precursor polymers and crosslinking mechanisms. Herein, we discuss the therapeutic outcomes of these hydrogels in terms of providing mechanical support, delivering cells/bioactive agents, regulating local inflammation, and promoting tissue regeneration and functional recovery.